Physical exercise for a healthy pregnancy: the role of placentokines and exerkines - Hamed Alizadeh Pahlavani; Ismail Laher; Katja Weiss; Beat Knechtle; Hassane Zouhal (Journal of Physiological Sciences)
Abstract Complications such as diabetes and preeclampsia can occur during pregnancy. Moderate-intensity exercise can prevent such complications by releasing placentokines and exerkines, such as apelin, adiponectin, leptin, irisin, and chemerin. Exercise and apelin increase thermogenesis and glucose uptake in pregnancy by activating AMPK, PI3K, PGC-1α, AKT1, UCP3, and sarcolipin. Exercise increases apelin levels to reduce preeclampsia symptoms by increasing eNOS, NO, placental growth factor (PlGF), and VEGF and decreasing levels of fms-like tyrosine kinase 1 (sFlt-1), soluble endoglin (sEng), and oxidative stress. A negative relationship has been reported between plasma leptin and VO2peak/kg and VO2peak in women with gestational diabetes. In active women, decreases in leptin levels reduce the risk of preeclampsia by ~ 40%. Higher adiponectin levels are associated with greater physical activity and lead to increased insulin sensitivity. Increased adiponectin levels in preeclampsia and exercise counteract inflammatory and atherogenic activities while also having vascular protective effects. Exercise increases irisin levels that correlate negatively with fasting glucose, insulin concentration, and glycosylated hemoglobin levels. Irisin augments mRNA expression levels of UCP1 and cell death-inducing DNA fragmentation factor-like effector A (cidea) to cause browning of adipose tissue, increased thermogenesis, and increased energy consumption. Irisin concentrations in mothers with preeclampsia in the third trimester negatively correlate with systolic and diastolic blood pressure. Expression levels of chemerin, IL-6, and TNF-α are increased in gestational diabetes, and the increases in chemerin in late pregnancy positively correlate with the ratio of sFlt-1 to PlGF as a marker of preeclampsia. The effects of physical exercise on placentokines and exerkines in women at various stages of pregnancy remain poorly understood.